Effect of Guided Imagery on Maternal Fetal Attachment in Nulliparous Women with Unplanned Pregnancy - Masoumeh Kordi; Maryam Fasanghari; Negar Asgharipour; Habibollah Esmaily (Mashhad University of Medical Sciences, 2016)
Introduction and Objectives: Nulliparous women with unplanned pregnancy experience high levels of anxiety, which may adversely affect maternal-fetal attachment. Therefore, in this study, we aimed to determine the effect of guided imagery on maternal-fetal attachment in nulliparous women with unplanned pregnancy. Materials and Methods: In this clinical trial, 67 nulliparous women with unplanned pregnancy were randomly divided into two groups of intervention (n=35) and control (n=32) in 2015. Data collection tools included a demographic form and London, DASS 21, and Cranley's maternal-fetal attachment questionnaires. In the intervention group, one session of guided imagery on maternal role was performed in 34th week of pregnancy in groups of four to seven. Afterwards, guided imagery CDs were given to mothers to be performed at home twice a week for two weeks; the control group only received the routine care. Maternal-fetal attachment was assessed before and two weeks after the intervention. To analyze the data, independent t-test, paired t-test, Chi-squared, Fisher's exact test, and Mann-Whitney U tests were run using SPSS version 21. Results: Maternal mean age was 24.1±4.3 years, and most mothers (49.3%) had high school education. Mean score of maternal-fetal attachment was significantly different between the intervention (94.26±6.7) and control (90.22 ± 9.5) groups after the intervention (P=0.04). Also, there was a significant difference between mean score of maternal-fetal attachment at the beginning and end of the intervention in the intervention and control groups (5.86±7.2 vs. 1.72±3.2; P=0.004). Conclusion: Guided imagery promoted maternal-fetal attachment in women with unplanned pregnancy; thus, it is recommended to use this method in prenatal care for these women.